2018
DOI: 10.1074/jbc.ra117.000852
|View full text |Cite
|
Sign up to set email alerts
|

Cross-kingdom auxiliary subunit modulation of a voltage-gated sodium channel

Abstract: Voltage-gated, sodium ion-selective channels (Na V ) generate electrical signals contributing to the upstroke of the action potential in animals. Na V s are also found in bacteria and are members of a larger family of tetrameric voltagegated channels that includes Ca V s, K V s, and Na V s. Prokaryotic Na V s likely emerged from a homotetrameric Ca 2+ -selective voltage-gated progenerator, and later developed Na + selectivity independently. The Na V signaling complex in eukaryotes contains auxiliary proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 103 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…NaVb1 is a promiscuous and multifunctional protein that (1) potentiates channel activity of the pore-forming voltagegated sodium channel a subunits, [43][44][45][46] (2) functions as a chaperone of sodium channel a subunits from the intracellular pool to the neuronal membrane, 47 (3) interacts with and modulates the activity of voltage-gated potassium channels, [48][49][50] and (4) acts as a cell adhesion molecule to enhance neurite outgrowth. 51 A population of NaVb1 subunits are localized at the axon initial segment, 52 as is NaV1.1.…”
Section: Therapeutic Mechanisms Of Aav-navb1mentioning
confidence: 99%
“…NaVb1 is a promiscuous and multifunctional protein that (1) potentiates channel activity of the pore-forming voltagegated sodium channel a subunits, [43][44][45][46] (2) functions as a chaperone of sodium channel a subunits from the intracellular pool to the neuronal membrane, 47 (3) interacts with and modulates the activity of voltage-gated potassium channels, [48][49][50] and (4) acts as a cell adhesion molecule to enhance neurite outgrowth. 51 A population of NaVb1 subunits are localized at the axon initial segment, 52 as is NaV1.1.…”
Section: Therapeutic Mechanisms Of Aav-navb1mentioning
confidence: 99%
“…In addition, CiNav1a was not affected by TipE. These findings are surprising given that it has been reported that the bacterial Nav channel can also be modified by mammalian β subunit ( 42 ). To explore why mammalian Nav1 β subunits fail to influence CiNav1a functions, we predicted a structure of CiNav1a bound to β1 by homology modeling (SWISS-MODEL) ( 8 , 43 , 44 ) based on cryo-EM structure of human Nav1.2–β2 complex (Protein Data Bank [PDB] ID: 6J8E ) and electric eel EeNav1.4–β1 complex (PDB ID: 5XSY ) ( 9 ).…”
Section: Discussionmentioning
confidence: 67%
“…At this stage, it remains unclear as to whether the site of binding is consistent between α subunits or indeed whether the binding interactions for β1 will be the same for β3 (Zhu et al, 2017). Interestingly, it was recently reported that the human β1 subunit can also interact with the bacterial NaChBac channel (Molinarolo et al, 2018) although the mode of interaction was not discussed.…”
Section: Introductionmentioning
confidence: 99%